Understanding adherence in virally suppressed and unsuppressed human immunodeficiency virus-positive urban patients on second-line antiretroviral treatment - Siphamandla B. Gumede; Willem D.F. Venter; Samanta T. Lalla-Edward (AOSIS, 2020)
Background: Understanding antiretroviral therapy (ART) adherence may assist in designing effective support interventions. Objectives: This study elicited perspectives on how to promote treatment adherence from virologically suppressed and unsuppressed patients receiving second-line ART. Methods: This was a cross-sectional study conducted with randomly selected patients active on second-line ART, from five public health facilities in the Johannesburg inner city. Data were collected on demographics, clinical information, participant's experiences and ART knowledge. Virological failure was defined as exceeding 1000 copies/mL. Results: The study sample comprised 149 participants; of which 47.7% (n = 71) were virally unsuppressed and 69.1% (n = 103) were women; the median age of the participants was 42 years (interquartile range [IQR] 36-47 years). Experiencing medication-related difficulties in taking second-line ART (p = 0.003), finding second-line regimen more difficult to take than a first-line regimen (p = 0.001) and experiencing side effects (p 0.001) were all subjective predictors of virological failure. Participants' recommendations for improving adherence included the introduction of a single tablet regimen (31.6%, n = 55), reducing the dosage to once daily (26.4%, n = 46) and reducing the pill size for second-line regimen (4.0%, n = 7). Conclusion: The results of this study highlight the importance of improving patients' knowledge about adherence and motivation to continue ART use despite the persistence of side effects and difficulties with taking medication.